TcTASV: a novel protein family in trypanosoma cruzi identified from a subtractive trypomastigote cDNA library. - Elizabeth A García; María Ziliani; Fernán Agüero; Guillermo Bernabó; Daniel O Sánchez; Valeria Tekiel (Public Library of Science (PLoS), 2010)
BACKGROUND: The identification and characterization of antigens expressed in Trypanosoma cruzi stages that parasitize mammals are essential steps for the development of new vaccines and diagnostics. Genes that are preferentially expressed in trypomastigotes may be involved in key processes that define the biology of trypomastigotes, like cell invasion and immune system evasion. METHODOLOGY/PRINCIPAL FINDINGS: With the initial aim of identifying trypomastigote-specific expressed tags, we constructed and sequenced an epimastigote-subtracted trypomastigote cDNA library (library TcT-E). More than 45% of the sequenced clones of the library could not be mapped to previously annotated mRNAs or proteins. We validated the presence of these transcripts by reverse northern blot and northern blot experiments, therefore providing novel information about the mRNA expression of these genes in trypomastigotes. A 280-bp consensus element (TcT-E element, TcT-Eelem) located at the 3' untranslated region (3' UTR) of many different open reading frames (ORFs) was identified after clustering the TcT-E dataset. Using an RT-PCR approach, we were able to amplify different mature mRNAs containing the same TcT-Eelem in the 3' UTR. The proteins encoded by these ORFs are members of a novel surface protein family in T. cruzi, (which we named TcTASV for T. cruzi Trypomastigote, Alanine, Serine and Valine rich proteins). All members of the TcTASV family have conserved coding amino- and carboxy-termini, and a central variable core that allows partitioning of TcTASV proteins into three subfamilies. Analysis of the T. cruzi genome database resulted in the identification of 38 genes/ORFs for the whole TcTASV family in the reference CL-Brener strain (lineage II). Because this protein family was not found in other trypanosomatids, we also looked for the presence of TcTASV genes in other evolutionary lineages of T. cruzi, sequencing 48 and 28 TcTASVs members from the RA (lineage II) and Dm28 (lineage I) T. cruzi strains respectively. Detailed phylogenetic analyses of TcTASV gene products show that this gene family is different from previously characterized mucin (TcMUCII), mucin-like, and MASP protein families. CONCLUSIONS/SIGNIFICANCE: We identified TcTASV, a new gene family of surface proteins in T. cruzi.